Zwitterion-functionalized dendrimer-entrapped gold nanoparticles for serum-enhanced gene delivery to inhibit cancer cell metastasis - Xiong, Zhijuan (2022)
We demonstrate a novel serum-enhanced gene delivery approach using zwitterion-functionalized dendrimer-entrapped gold nanoparticles (Au DENPs) as a non-viral vector for inhibition of cancer cell metastasis in vitro. Poly(amidoamine) dendrimers of generation 5 decorated with zwitterion carboxybe taine acrylamide (CBAA) and lysosome-targeting agent morpholine (Mor) were utilized to entrap gold NPs. We show that both Mor-modified and Mor-free Au DENPs are cytocompatible and can effectively deliver plasmid DNA encoding different reporter genes to cancer cells in medium with or without serum. Strikingly, due to the antifouling property exerted by the attached zwitterion CBAA, the gene delivery efficiency of Mor-modified Au DENPs and the Mor-free Au DENPs in the serum-containing medium are 1.4 and 1.7 times higher than the corresponding vector in serum-free medium, respectively. In addition, the Mor-free vector has a better gene expression efficiency than the Mor-modified one although the Mor modification enables the polyplexes to have enhanced cancer cell uptake. Wound healing and hyperme thylated in cancer 1 (HIC1) protein expression assay data reveal that the expression of HIC1 gene in cancer cells enables effective inhibition of cell migration. Our findings suggest that the created zwitterion-functionalized Au DENPs may be employed as a powerful vector for serum-enhanced gene therapy of different diseases.